2020
DOI: 10.20472/te.2020.8.2.002
|View full text |Cite
|
Sign up to set email alerts
|

What Motivates Students to Study in Upper Secondary School? A Study on Students’ Perspective on Study Motivation in Four Different Study Programs in Sweden

Abstract: Every fourth student in Sweden cancels their upper secondary school education, although the intention behind the new school reform 2011 (GY-11) was to increase the throughput. One important reason for this is a lack of study motivation, which, in turn, has different causes. The authors of this study have chosen to focus on students' perceptions of what is happening in the classroom (i.e., learning and teaching in four different study programs). The purpose of the article is to describe and analyze students' pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…Our aim was to describe and analyse variations in the ways the students in three types of study programmes (a total of six programmes) conceptualized study motivation. Our results validated our previous findings (Boström & Bostedt, 2020a, 2020b that students believe that their learning strategies, teachers' teaching strategies, learning environment, and other factors in their immediate surroundings are important for their motivation to study. This is in accordance with Hatties's (2009) findings that teacher-student interaction and the teachers' overall didactic competence are crucial, as well as Blomgren's (2016) findings that students' perspectives on schoolwork are important for motivation and Szklarskis's (2011) argument that students' interest in and progress in their studies are important.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our aim was to describe and analyse variations in the ways the students in three types of study programmes (a total of six programmes) conceptualized study motivation. Our results validated our previous findings (Boström & Bostedt, 2020a, 2020b that students believe that their learning strategies, teachers' teaching strategies, learning environment, and other factors in their immediate surroundings are important for their motivation to study. This is in accordance with Hatties's (2009) findings that teacher-student interaction and the teachers' overall didactic competence are crucial, as well as Blomgren's (2016) findings that students' perspectives on schoolwork are important for motivation and Szklarskis's (2011) argument that students' interest in and progress in their studies are important.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, access to student health is a crucial factor for students to increase their study motivation. Results of current Swedish research projects (Boström & Bostedt, 2020a, 2020b show that students believe that their learning strategies are crucial but also that teaching strategies, the learning environment, and other factors in their immediate environments are important. We found some similarities between the four upper secondary programs that we included, such as a preference for more practically oriented pedagogy, shortterm goals and quick feedback, varied teaching methods, and good textbooks.…”
Section: Previous Researchmentioning
confidence: 99%
“…They confirmed that learners in EFL classes exhibited both instrumental and integrative motivation. These findings were supported by Boström & Bostedt (2020), who discovered that motivation was essential for successful writing. These findings are also consistent with those of other studies that have shown that motivation plays an important role in EFL classes (Agustrianti, et al 2016;Nasihah & Cahyono, 2017;Nailufar, 2018;Jianfeng, 2018;Abas & Aziz, 2018;Al-Ta'ani, 2018;Nguyen & Walkinshaw, 2018;Elhawwa, 2019;Surastina & Dedi, 2018;Bai & Guo, 2019;Aspuri et al, 2019;Rathiga & Sarpparaje, 2019;Budiharto & Amalia, 2019;Nurbaety & Hartini, 2020;Samah, 2021;Abir & Shazed, 2022;Budiharto & Amalia, 2019;Wright, et al, 2020).…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, Boström and Bostedt (2020) proved that motivation affects students' ability to focus on desired goals. High-achieving secondary school students, for example, have favorable outcomes in future higher education.…”
mentioning
confidence: 99%
“…These teachers have the background to differentiate content, deviate from the textbook's structure, and engage in various instruction strategies, such as in-depth discussions, with their students. Current research from Sweden (Boström & Bostedt, 2021, based on students' voices regarding whether the teacher influences their motivation, has shown, on the contrary, that students value the teacher's personality more than their competence in relation to being motivated.…”
Section: Previous Researchmentioning
confidence: 98%